Unveiling the prevalence of anaemia and its predictors among adults on highly active antiretroviral therapy in the dolutegravir era: a retrospective cross-sectional study - Pradeep Singh; Woretaw Sisay Zewdu; Mulugeta Molla Zeleke; Yared Andargie Ferede; Achenef Bogale Kassie; Muluken Adela Alemu; Getaye Tessema Desta (BMJ Open)
Objective This study examined the prevalence, severity and risk factors of anaemia among adult people living with HIV attending an antiretroviral therapy centre in Woreta Primary Hospital, Woreta town, Ethiopia.Design Hospital-based retrospective cross-sectional study.Setting Public health facility that provides HIV care in Woreta town.Participants A total of 289 medical records of adults living with HIV/AIDS on highly active antiretroviral therapy from February 2019 to September 2023 at government hospital were reviewed using a systematic sampling method. The data were entered using Epi-info V.7 and exported to SPSS V.23 for data analysis. The data were analysed using bivariate and then multivariate logistic regression models in order to identify variables associated with anaemia. At the 95% CI level, variables having a p value of <0.05 were deemed to be statistically significant predictors.Primary outcome Prevalence and severity of anaemia and its predictors among adult patients living with HIV on antiretroviral therapy in Woreta Primary Hospital.Results The total prevalence of anaemia was 31.5% (95% CI 28.9 to 33.8). The prevalence of mild, moderate and severe anaemia was 20.42%, 10.38% and 0.70%, respectively. Predictors independently linked with anaemia were female sex (adjusted OR (AOR) 1.08), age ≥40 years (AOR 1.21), lived with HIV >10 years (AOR 2.31), CD4 counts <200 cells/µL (AOR 3.81), non-suppressed viral load (AOR 1.28), history of opportunistic infections (AOR 1.54), WHO clinical stages III and IV (AOR 1.37 and 2.23, respectively) and history of parasitic infestation (AOR 2.81).Conclusions A sizeable proportion of participants were found anaemic. Female sex, older age, longer periods lived with the virus, lower CD4 count, non-suppressed viral load, history of opportunistic infections, WHO clinical stages III and IV and history of parasitic infestation were the contributing factors. Therefore, to improve the anaemic status and living circumstances of patients living with HIV, immediate action on the linked factors is needed, such as monitoring for maintenance of CD4 counts >200 cells/μL and avoiding progression of HIV to the advanced WHO clinical stages, suppressed viral load, preventing opportunistic infections and parasitic infestation.